Longitudinal assessment of virological failure and antiretroviral drug resistance among treatment-naïve subjects living with HIV - Mendes Marcon, Chaiana Esmeraldino; Schlindwein, Aline Daiane; Schuelter-Trevisol, Fabiana (Current HIV research, 2023)
Human immunodeficiency virus (HIV) infection, the etiological agent of acquired immunodeficiency syndrome (AIDS), is a serious public health issue. Therapeutic measures have been successful in increasing the survival and improving the quality of life. However, some treatment-naive subjects living with HIV present resistance-associated mutations as a result of late diagnosis and/or mutant strain infections. The objective of this study was to identify the virus genotype and assess the antiretroviral resistance profile based on the results of HIV genotyping in treatment-naive subjects living with HIV, after six months of taking antiretroviral therapy. This was a prospective cohort study on treatment-naive adults living with HIV attending a specialized outpatient clinic in southern Santa Catarina State, Brazil. The participants were interviewed and had blood samples drawn. The genotypic antiretroviral drug resistance profile was examined in patients with detectable viral loads. 65 treatment-naive subjects living with HIV were recruited for this study. After six months of taking antiretroviral therapy, resistance-associated mutations were observed in 3 (4.6%) subjects living with HIV. Subtype C was identified as the circulating subtype in southern Santa Catarina State, and L10V, K103N, A98G, and Y179D were the most common mutations found in treatment-naive subjects.